Research on the Development of Thermal Insulation Mortar - He, Shaokun (International Journal of Materials Science and Technology Studies, 2026)
Building energy consumption accounts for approximately 35%–40% of global total energy use, making the improvement of envelope thermal performance a key strategy for building energy efficiency. Thermal insulation mortar has been widely used in building energy renovation due to its convenient construction, relatively low cost, and good compatibility with substrate walls. Although traditional lightweight aggregate thermal insulation mortars (e.g., expanded perlite, glazed hollow beads, EPS particles) can reduce thermal conductivity, they suffer from high water absorption, low compressive strength, drying shrinkage cracking, and insufficient long-term durability, which limit their application in high-performance energy-saving systems. In recent years, research has increasingly shifted toward aerogel-based thermal insulation cementitious composites. Aerogel, featuring a nanoporous structure, ultra-low density, and extremely low thermal conductivity, significantly reduces the thermal conductivity of mortar, enabling lightweight and highly efficient thermal insulation. However, the incorporation of aerogel also leads to a marked decline in mechanical properties, primarily due to the low strength of aerogel itself and the weak interfacial bonding between its hydrophobic surface and the cement paste, which tends to form interfacial transition zone defects and pore-rich regions. To address these challenges, researchers have focused on several aspects, including mix proportion design to balance thermal and mechanical performance by adjusting aerogel content, water-to-binder ratio, and admixtures; interface modification using silane coupling agents, dispersion aids, and low-shear mixing to improve compatibility and dispersion uniformity between aerogel and the cement matrix; fiber reinforcement through the introduction of polypropylene (PP), PVA, basalt and other fibers to bridge cracks, enhance toughness, and compensate for strength loss and cracking tendency; and multi-performance synergistic evaluation extending from single thermal conductivity testing to comprehensive assessments covering water absorption, drying shrinkage, freeze–thaw cycling, high-temperature stability, crack resistance, and long-term durability. Furthermore, international research has extended aerogel thermal insulation mortar to fire resistance and extreme environment applications, such as tunnel fire protection, industrial insulation, and structural thermal protection under high temperatures. Overall, research on thermal insulation mortar has evolved from traditional lightweight aggregate systems toward aerogel-based high-performance composites, with the focus shifting from simply reducing thermal conductivity to synergistic optimization of thermal, mechanical, and durability properties. Nevertheless, challenges remain in terms of high aerogel cost, insufficient interfacial bonding, difficulties in large-scale preparation, and lack of engineering application standards. Future research should focus on low-cost aerogel production, interface strengthening, multiphase composite reinforcement, long-term service performance evaluation, and construction technique optimization, so as to promote the transformation of thermal insulation mortar toward a multi-functional integration of thermal insulation, crack resistance, durability, and structural compatibility.